High genotypic diversity of the reef-building coral Porites lobata (Scleractinia: Poritidae) in Isla del Coco National Park, Costa Rica - Boulay, Jennifer N. (2012)
The isolated Isla del Coco experiences periodic, extreme disturbances which devastate coral reefs surrounding the island. Scleractinian corals build the physical structure of the reef therefore ecosystem recovery relies on coral species recovery. Coral recruits can be of sexual or asexual origin, and the relative success of the two recruit types influences the speed and spread of recovery processes. Here we focus on the massive coral, Porites lobata, because it is the main reef-builder around Isla del Coco to describe the relative contribution of asexual and sexual recruits to population maintenance. P. lobata samples were collected using a spatially explicit random sampling design in three plots at Isla del Coco: Punta Ulloa (n=17), Bahía Weston (n=20) and Punta María (n=20) and samples were genotyped with 11 microsatellite markers. Additional sampling was conducted at three “coastal” sites near the Costa Rican mainland (Isla del Caño Biological Reserve): Caño1 (n=8), Caño2 (n=10), Caño5 (n=11) to compare the contributions of asexual and sexual recruits at Isla del Coco sites to coastal sites. Isla del Coco sites were characterized by small colony size (>60% of colonies <0.5m2) and high sexual reproduction. Sites were either mostly or entirely sexual,consisting of only unique genotypes (NG/N= 0.90-1.00; G O/GE=0.83-1.00; D=0.99-1.00). Although there were no significant differences in genetic diversity (number of alleles per locus, number of private alleles) or colony size between Isla del Coco and the coastal sites, the coastal sites exhibited a greater range of genotypic diversity from moderately asexual (NG/N=0.5; GO/GE=0.36; D=0.8) to purely sexual (NG/N=1.0; GO/GE=1.0; D=1.0). The mode of asexual reproduction in P. lobata is likely fragmentation of adult colonies rather than asexual larval production because ramets of P. lobata occurred close together and asexually produced larvae have not been reported in gonochoric broadcast spawners like P. lobata. Frequent sexual reproduction at Isla del Coco National Park might represent a resource for rapid recovery following extreme El Niño-Southern Oscillation (ENSO) disturbance events. In contrast, larger, asexuallyproduced fragments rather than smaller, sexually-produced larvae appear to have the advantage at some coastal sites. The high frequency of sexual reproduction at Isla del Coco indicates that not only are sexual partners available but also current conditions are favorable for the delivery of larvae and the rate of predation on small larval recruits must be moderate. Citation: Boulay, J.N., J. Cortés, J. Nivia-Ruiz & I.B. Baums. 2012. High genotypic diversity of the reef-building coral Porites lobata (Scleractinia: Poritidae) in Isla del Coco National Park, Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 279-292. Epub 2012 Dec 01.